The Realities of Auditor's Independence and Objectivity - M. Krishna Moorthy; A. Seetharaman; A. S. Saravanan (Journal of Accounting, Business and Management (JABM), 2010)
This study looks at the issue of the auditors independence to gauge whether their independence is a fact or a mere fiction? Due to the controversial fall of Enron and accounting giant Arthur Andersen, the auditing profession has been looked down upon and auditors reputation is going down day by day. In situations when the management is true and honest, the relationship between the management and the auditor is more collaborative and the auditor can complete the assignment to his/her satisfaction. However, in some situations, the relationship between the auditors and the management may be antagonistic and anecdotal evidence suggests that, in such situations, client pressure on auditors may constitute a threat to their independence and objectivity. Understanding how client preferences impact audit judgments is also important because such preferences may lead an auditor to accept an inappropriate accounting treatment. A client preference communicated earlier in the evaluation process may prevent the auditor from giving an unbiased assessment. As auditors anticipate and justify their judgements to others, they look for evidence to support the client preference or to refute it.